First you need the farmers: The microfarm system as a critical intervention in the alternative food movement - Curtis, Kent; Hand, Grace (Journal of Agriculture, Food Systems, and Community Development, 2024)
After more than three decades, the alternative food movement has developed multiple strategies, most of which are still struggling. This essay surveys the literature on six key alternative food movement (AFM) strategies, assessing their strengths and weaknesses before describing a novel strategy, the microfarm system, which is being implemented in north central Ohio. It argues that key omissions from most AFM scholarship and practices include sustained attention to training and supporting successful farmers, concerted efforts to help facilitate needed social networks or communities of practices around alternative food developments, and forwarding a set of ambitions that do not appreciate the scale of existing food systems nor the limits of alternative food systems’ impact. It offers the microfarm system as an emerging approach to address these omissions.